1991
DOI: 10.1537/ase1911.99.411
|View full text |Cite
|
Sign up to set email alerts
|

The Bushman Maxillary Canine of the Chewa Tribe in East-Central Africa.

Abstract: The expression of the Bushman Canine dental trait among the Chewa tribe of East-Central Africa is described and compared with that of other African populations. Dental hard stone casts were obtained from 82 males and 76 females, and the trait was scored using the Arizona State University dental plaque system. No significant sexual dimorphism in the occurrence of the trait was found according to the chi-square test. The frequency of the Bushman Canine in the Chewa is markedly lower than that in a sample of San … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…All traits were previously found to be largely independent of one another (Nichol, 1990). ASUDAS procedures are based on well-established criteria for scoring intratrait variation, and proved reliable in many preceding studies (e.g., Scott, 1973Scott, , 1980Turner, 1985aTurner, , 1987Turner, , 1992Sakuma and Ogata, 1987;Sakuma et al, 1991;Haeussler et al, 1988;Turner and Markowitz, 1990;Irish and Turner, 1990;Irish, 1993Irish, , 1994Irish, , 1997Irish, , 1998aIrish, -d, 2000Jackes et al, 2001). Traits are recorded using 23 rank-scale reference plaques that help standardize scoring by providing representations of minimum, maximum, and common intermediate expressions (Turner et al, 1991).…”
Section: Dental Trait Recordingmentioning
confidence: 99%
“…All traits were previously found to be largely independent of one another (Nichol, 1990). ASUDAS procedures are based on well-established criteria for scoring intratrait variation, and proved reliable in many preceding studies (e.g., Scott, 1973Scott, , 1980Turner, 1985aTurner, , 1987Turner, , 1992Sakuma and Ogata, 1987;Sakuma et al, 1991;Haeussler et al, 1988;Turner and Markowitz, 1990;Irish and Turner, 1990;Irish, 1993Irish, , 1994Irish, , 1997Irish, , 1998aIrish, -d, 2000Jackes et al, 2001). Traits are recorded using 23 rank-scale reference plaques that help standardize scoring by providing representations of minimum, maximum, and common intermediate expressions (Turner et al, 1991).…”
Section: Dental Trait Recordingmentioning
confidence: 99%
“…Key words: Deciduous canine, permanent canine, crown morphology, tooth size, crown index (Leutenegger, 1976;Leutenegger and Kelly, 1977;小木曽,1982;Greenfield, 1990;Sakuma et al, 1991 (Ward et al, 2001) や Australopithecus africanus の 研 究 (Moggi-Cecchi et al, 1998 (Johanson, 1974;酒井・高橋, 1985;Plavcan, 1993 (Schultz, 1958;Frisch, 1963;Garn et al, 1967 Pan paniscus(Male) 72.9 Johanson, 1974 Pan paniscus(Female) 72.5 Johanson, 1974 Pan troglodytes(Male) 68.4 山田,未発表 Pan troglodytes (Female) 74.2 山田,未発表 Au. afarensis (Hadar) 80.7 Johanson et al, 1982 Au.…”
mentioning
confidence: 99%
“…Numerous studies have shown that the trait is entirely absent or occurs in very low frequencies in non-African populations (e.g., Morris, 1975;Turner 1985Turner , 1992aIrish, n.d.;Hawkey, personal communication, 1994;Hemphill, personal communication, 1994). However, it occurs in up to 40+ percent of southern African Khoisan-speaking peoples (i.e., San and Khoikhoi), and exhibits a significant Pan-African distribution (see Morris, 1975;Sakuma et al, 1991;Irish, 1993Irish, , 1994Irish, , 1995Irish and Turner, 1990). Therefore, we feel that the trait's definition should be reiterated to help prevent future misidentification by dental researchers and thus maintain its utility as part of a diagnostic suite of African dental attributes (see Irish, 1993Irish, , 1994Irish, , 1995.…”
mentioning
confidence: 99%